Mastering leadership : an integrated framework for breakthrough performance and extraordinary business results - Anderson, Robert J., 1955-; Adams, William A. (Gildan, 2019)
Is your leadership a competitive advantage, or is it costing you? How do you know? Are you developing your leadership effectiveness at the pace of change?